DESIGNING A VTUBER CHARACTER BASED ON INDONESIAN FOLKLORE TO ENHANCE YOUTH INTEREST IN LOCAL CULTURE - Christopher Owen Setiawan; Aristarchus Pranayama; Rebecca Milka Natalia Basuki (Jurnal Pilar Nusa Mandiri, 2026)
Indonesian folklore contains rich cultural values, yet its relevance to Generation Z is declining due to their preference for digital content consumption. Modern media such as animations or games are no longer effective to capture their attention, creating a gap in how folklore is introduced to younger audiences but not for older audiences. This study explores the use of Virtual YouTubers (VTubers) as a medium to adapt and present folklore in ways that align with Gen Z’s digital lifestyle. Dewi Sekartaji, a character from the Panji folklore of East Java, is reimagined as a VTuber whose personality emphasizes patience and perseverance. The objective is to preserve folklore while fostering cultural pride and introducing new perspectives from side characters to Gen Z. User testing showed an average satisfaction score of 4.8/5, and the Character livestream attracted around 500 viewers, indicating that VTubers are an effective approach for bridging traditional culture with modern digital engagement.